Pengaruh Iklan, Diskon dan Teman Sebaya Terhadap Impulse Buying Dalam Pembelian Produk Fashion - Harpepen, Andi (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to determine the effect of advertising, discounts and peers on impulse buying in the purchase of Fashion Products, with a sample of 99 students of IAIN Bengkulu. The analysis technique used in this research is multiple linear regression. The results showed that partially advertising, discounts and peers have an effect on impulse buying, while simultaneously advertising, discounts, and peers have an effect on Impulse Buying with a large effect of 63.2% and 36.8% influenced by other factors outside the study